Formation of Communication Facilities in the Media - Khismatullina, Regina B.; Goryacheva, Olga N.; Gunko, Oksana G. (Journal of History Culture and Art Research, 2018)
The article concerns the factors of the formation of communicative attitudes, linguistic security, and speech aggression in the media. Studying the language characteristics of modern society, the authors analyze regressive phenomena in the information and communication environment. The influence of journalistic texts on the worldview of readers of the modern press is manifested in the changing information background. Of particular interest is the influence of connotations on the media text and on postindustrial society in general. Considering the communicative process in the media taking into account the linguistic traditions, the connection of generations, ethnic unity, the authors identify specific ways of communication that evolve under the influence of a changing information environment. The relevance of the study consists in revealing the forms of manifestation of speech aggression in the texts of print media. Given that the perception of media text takes into account background information, it is assumed that negative communication patterns are being formed in the society, with special focus on the examples containing a violation of communicative and ethical norms. The practical importance of the study of the formation of communicative attitudes in the media is connected with the careful study of journalistic materials and the definition of the quality characteristics of means of influence on the audience of the media.